Perspectives of construction workers on the management of Concrete Waste on Construction Sites: A Case study of Ho Municipality, Ho, Ghana - George Harrison Coffie; Raymond Kirk Apawu; Jonas Ekow Yankah (Journal of Building Materials and Structures, 2025)
Many countries worldwide are experiencing rapid population expansion and urbanization, which increase building activity and, therefore, waste generation. To reduce and manage waste, a thorough understanding of the factors that contribute to its formation is required. This study examines concrete waste management on construction sites in the Ho Municipality of Ghana. The purpose is to examine the reasons behind on-site concrete waste and the techniques for managing it. The study's findings demonstrated that the main factors contributing to on-site concrete waste were rework because of broken equipment, workmanship error, negligence, and supervisor neglect of inspection. The recycling of concrete waste generated on-site, disposal of concrete waste generated at permitted landfills, and reuse of concrete waste generated on-site are the most efficient means of handling and disposal of concrete waste on-site. The study discovered that training workers on ways to handle concrete to avoid wastage, using proper mix during production to avoid waste, and proper and effective supervision when producing and placing concrete were efficient ways of minimizing concrete waste at construction sites. The study recommended that an adequate construction waste management plan is required to aid professionals in minimizing waste and to involve all other stakeholders in such a plan.